Author Correction: Physico-chemical properties based differential toxicity of graphene oxide/reduced graphene oxide in human lung cells mediated through oxidative stress. Issue 1 (December 2018) - Mittal, Sandeep; Kumar, Veeresh; Dhiman, Nitesh; Chauhan, Lalit; Pasricha, Renu; Pandey, Alok
A correction has been published and is appended to both the HTML and PDF versions of this paper. The error has not been fixed in the paper.